Agro-morphological Characterization of Bangladeshi Aromatic Rice (Oryza sativa L.) Germplasm Based on Qualitative Traits (Bangladesh Rice Journal, 2019)
The agro-morphological characterization of germplasm is of utmost importance to generate information to be utilized in plant breeding programmes. The aim of this study was to characterize the agro-morphological traits of 113 accessions of aromatic germplasm (Oryza sativa L.) based on qualitative agro-morphological descriptors. No duplicates were identified among the studied accessions for qualitative traits in the cluster analysis, which means there is a high diversity among the accessions for these traits. Following UPGMA cluster analysis, 113 accessions of aromatic germplasm formed ten distinct clusters. The highest numbers of germplasm (96) were found in cluster IXd, 2 were found in cluster III, IV and VI, 3 were found in IXc and the lowest number of germplasm (1) in cluster I, II,V, VII, VIII, IXa, IXb and X, respectively. Aroma evaluation revealed that 67 germplasm were scented, 34 were lightly scented, while the rest 12 germplasm were nonscented. Germplasm namely Begun bichi, Elai, Chinigura, Basmati 370, Ranisalut, Sakkorkhora, Jirakatari, Raduni Pagal, Kalijira (long grain), Black TAPL-554, Kalgochi, BRRI dhan34, BRRI dhan50, Badshabhog-2, Tulsimala-2, Kataribhog, BU dhan2R , Sakkorkhana, Maloti, Bashful could be used for further improvement for incorporating aroma to the high yielding varieties.Bangladesh Rice j. 2018, 22(2): 41-54